Tehnik Penyusunan Rencana Usaha Kecil Menengah (Ukm) Komunitas Perempuan Kepala Rumah Tangga (Pekka) Masjid Agung Palembang - Chandra Satria; Doly Nofiansyah (AKM, 2021)
The community service activity entitled "Techniques for Preparing Small and Medium Enterprises (UKM) Community Heads of Households (PEKKA) of the Great Mosque of Palembang" for Entrepreneurs of the Community Head of Household (PEKKA) of the Great Mosque of Palembang Foundation was held on Sunday, November 15. 2020 through offline training facilities and a food festival activity planned for ethnic food (traditional food) in the Great Palembang mosque environment according to the time and permission of the Covid 19 group of South Sumatra Province. . The training material is in the form of strengthening the level of business production, product packaging, product marketing using digital placed markets, as well as simple financial bookkeeping which provides brief reports related to business management in monitoring the financial angle.